Difficulty in Comprehending British and American Lexicology for Indonesian Student - M. Nazar (Budapest International Research and Critics University, 2022)
In this chapter, we have tried to show that the vocabulary of English is in reaality a collection of ‘vocabularies’. While all speakers off the language share a ‘common core’ of words, each one also has access, either solely as a reader/ listener, or additionally as a writer / speaker, to a number of ‘specialist vocabularies’. The specialist vocabularies can be identified along a number of dimensions of variation of variation, including: geography, giving national and regional (dialect) varieties; occupation and interest, giving ‘jargons’; sub- culture, giving types of ‘slang’; and formality. The chapter concluded with a brief look at restricted languages, such as those used for air and sea navigation.